A problemática da constituição da ofensa no ato de insultar : a injúria como prática linguística discriminatória no Brasil = The issue of setting up the offense in the act of insulting : injury as a linguistic discriminatory practice in Brazil - Santos, Karla Cristina dos, 1980- (2012)
Orientador: Kanavillil Rajagopalan